Changes in maternal body composition, development of the conceptus and estimation of energy requirements for pregnant crossbred Holstein x Gyr cows - Sguizzato, Anna Luiza Lacerda (2018)
This study aimed to evaluate the effects of plane of nutrition and advancing days of pregnancy (DP) on maternal body composition, fetal development and energy requirements of pregnant crossbred Holstein × Gyr cows. Differing planes of nutrition were established by two feeding regimes (FR): ad libitum (AL) or maintenance (MA). Sixty-two nonlactating multiparous Holstein × Gyr cows with average body weight (BW) of 480 ± 10.1 kg and an age of 5 ± 0.5 years were used. Cows were divided into three groups: pregnant (n = 44), non-pregnant animals (n = 12), and base line reference cows (n = 6). The 56 pregnant and non-pregnant cows were randomly allocated into two different FR: AL and MA. Cows fed at MA received 1.15% of their BW on a dry matter (DM) basis. Receiving corn silage and a concentrate-based diet at a ratio of 93:7 on a DM basis. Reference group cows were slaughtered at the beginning of the experimental period to estimate body composition and empty body weight (EBW). To evaluate the effects DP, pregnant and non- pregnant animals were slaughtered at day 140, 200, 240, and 270 of gestation. Feeding regimen affected maternal tissue (MT) composition and DP changed fresh weight (FW), DM and energy content, but no differences were observed for crude protein (CP) and ether extract (EE) in response to DP. Feeding regimen affected mammary gland components (CP, EE, and energy content), but not fresh or dry weights. Days of pregnancy influenced almost all mammary gland components, except energy content. In regard to the uterus, FR affected only fresh and dry weights; however, DP impacted every uterus component measured. The only interaction between FR and DP in this study was observed for placental fresh weight. Cows fed AD on d 270 presented the same placental FW as cows at MA and AD on d 200 and 240. Further, pregnant cows fed at MA on d 270 had greater placental FW than cows fed AD at this day. Days of pregnancy, but not FR, influenced composition of fetal fluids in pregnant cows. Finally, cows fed at MA had greater FW for fetus than cows fed AD; however, fetus composition changed over DP. It was observed an increase for FW, DM, EE and energy content until day 270, but a decrease in CP. Requirements for maintenance did differ between pregnant and non- pregnant cows, thus two equations were developed. Net energy (NE) and metabolizable energy (ME) requirements for maintenance of non-pregnant cows estimated in this study were 81 kcal/EBW 0.75 /d and 131 kcal/EBW 0.75 /d, respectively. The efficiency of use of ME for maintenance of non-pregnant cows was 61.8%. Net energy and ME for maintenance of pregnant cows were 85 kcal/EBW 0.75 /d and 136 kcal/EBW 0.75 /d, respectively. Efficiency of use of ME for maintenance of pregnant cows was 62.5%. Estimates of net energy for gain (NE g ) were different using non- pregnant and pregnancy cows’ data, thus non-pregnant cows’ requirements are recommended. The efficiency of use of ME for gain was 41.9%. Energy requirements for pregnancy were estimated fitting energy in gestation components (Mcal) in function of DP using a non-linear regression. The efficiency of use of ME for pregnancy was 15%. Furthermore, net energy for pregnancy was statistically significantly different from zero from day 70 of pregnancy. In conclusion, the novelty of our data presents specifically how changes due to feeding regime and days of pregnancy occur in maternal tissues and the conceptus. Net energy and ME for maintenance of non-pregnant Holstein × Gyr cows are different from pregnant cows. Regarding NE g , we recommend estimating it only with data from non-pregnant animals. Furthermore, we believe that the proposed non-linear equations to estimate net energy requirements for pregnancy are more adequate and should be recommended for Holstein × Gyr cows.